Analyzing the relationship between accounting firms and ISA220 in the healthcare system: This study is exploratory (Entrepreneurship Journal for Finance and Business, 2026)
The research aims to bring together work offices and adjust certain machine and system settings and their relationship to security elements to ensure the quality of integration services in the field. We investigated the following hypothesis: "There is no significant correlation or influence between the application of the International Auditing Standard (ISA220) and its validity."The researchers prepared the practical aspect of the research by distributing (98) questionnaires to a number of auditors in private audit offices and companies, in order to determine the extent of the relationship and impact achieved by the policies and procedures of the quality control standard in enhancing competitive advantage. One of the most prominent conclusions is that the adoption of the ISA 220 standard by audit offices represents a key factor in achieving competitive advantage, as it contributes to raising the level of audit quality and reducing risks.